2013
DOI: 10.1364/oe.21.008746
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the physical mechanism of generation of coherent N_2 ^+ emissions in air by femtosecond laser excitation

Abstract: Recently, amplification of harmonic-seeded radiation generated through femtosecond laser filamentation in air has been observed, giving rise to coherent emissions at wavelengths corresponding to transitions between different vibrational levels of the electronic B(2)Σ(u)(+) and X(2)Σ(g)(+) states of molecular nitrogen ions [Phys. Rev. A. 84, 051802(R) (2011)]. Here, we carry out systematic investigations on its physical mechanism. Our experimental results do not support the speculation that such excellent coher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 22 publications
3
63
2
4
Order By: Relevance
“…It is noteworthy that although the existence of population inversion has been confirmed with systematic experimental investigations, the mechanism behind the establishment of the inverted population within an ultra-short period of only ~100 fs is still under hot debate. In fact, several models have been proposed to understand the physics of such air laser, including stimulated emission based on seed amplification in a population inverted system, four-wave mixing, and seed-triggered superradiance [17][18][19][20]. Nevertheless, none of these models has been completely confirmed and widely accepted.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that although the existence of population inversion has been confirmed with systematic experimental investigations, the mechanism behind the establishment of the inverted population within an ultra-short period of only ~100 fs is still under hot debate. In fact, several models have been proposed to understand the physics of such air laser, including stimulated emission based on seed amplification in a population inverted system, four-wave mixing, and seed-triggered superradiance [17][18][19][20]. Nevertheless, none of these models has been completely confirmed and widely accepted.…”
Section: Introductionmentioning
confidence: 99%
“…As for its photon the energy is 1.3 eV, then for multiphoton ionization of molecular nitrogen in the upper laser level (18.7 eV) requires the 15 photons (Figure 6). Thus the excess energy above B 2 Σ u + (v=0) state is 0.88 eV, while in the work with λ = 800 nm [11,12,[15][16][17] 13 photons requires, which gives a total energy of 20.15 eV and exceeding of the upper laser level at 1.45 eV. I.e.…”
Section: Discussionmentioning
confidence: 92%
“…For lasing at the aforementioned wavelengths the wavelength of the third or fifth harmonics of a pump laser should be coincided with them. It was later shown that the generation at these transitions occur and with femtosecond laser pump at a 800 nm wavelength in the presence of a second laser operating at a wavelength near 400 nm [11,12]. In the latter case the second laser is an analog of the third or fifth harmonic of pump laser operating in the mid-IR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several models have been proposed to interpret the physics of such air lasers, including stimulated emission based on seed amplification in a population-inverted system, four-wave mixing, and seedtriggered super-radiance, etc. [11][12][13][14][15]. In particular, Kartashov et al recently proposed that the different rotational periods of aligned molecular ions on the ground and excited electronic states can lead to transient laser gain and thus the creation of bright narrow-bandwidth coherent UV emissions in suitable time windows [15].…”
Section: Introductionmentioning
confidence: 99%